Improved recurrent NARX neural network model for state of charge estimation of lithium-ion battery using pso algorithm - Hossain Lipu M.S.; Hussain A.; Saad M.H.M.; Ayob A.; Hannan M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Backpropagation; Charging (batteries); Errors; Industrial electronics; Ions; Lithium-ion batteries; Mean square error; Particle swarm optimization (PSO); Recurrent neural networks; Temperature; Back-propagation neural networks; Drive cycles; Lithium ions; NARX neural network; Nonlinear AutoRegressive with eXogenous input models; Particle swarm optimization algorithm; State of charge; State-of-charge estimation; Battery management systems